Problems experienced by selected beginning teachers with implications for pre-service and in-service teacher education - Balais, Bonifacia N. 1927- (s.n.], 1967)
The problems experienced by beginning teachers particularly from the 1965 graduates of the Zamboanga Normal College are sought in this study and the relationship between these problems and selected variables, such as, achievement in professional education courses, school locality, and grade level taught by the new teacher are also investigated. The implications to pre-service and in-service teacher education are drawn based on the findings of the study.